Design of electro-hydraulic servo loading controlling system based on fuzzy intelligent water drop fusion algorithm. (October 2018) - Xuan, Wu; Fanquan, Zeng
Abstract: The aim of this study is to improve the reasonability of electro-hydraulic servo loading controlling design and enhance motor performance. Therefore, the electro-hydraulic servo loading controlling and multiple-objective optimisation design method for the intelligent water drop algorithm (IWD), which is based on a two-phase weight balance and multiple-objective, is proposed. First, research is conducted on the electro-hydraulic servo loading controlling design by selecting two indexes to carry out the object design. Second, the two-phase multiple-objective IWD algorithm is designed; in the first phase, two knowledge bases are adopted for the IWD swarm position initialisation, namely, IWD flying direction designation and reference point storage. In the second phase, the weighted equalisation method is adopted to reform the optimised intensive search process, to ensure the diversity of IWD algorithm swarm and reference point position to enhance the search performance. Finally, the effectiveness of the proposed method is validated through a simulation experiment.